Pengaruh DPK, NPF, CAR, ROA, dan REO Pada Pembiayaan yang Disalurkan BPRS di Indonesia - Chanda Fawwaz Mahesa; Mochamad Edman Syarief; Anita Putri; Raya Puspita Sari Hasibuan (Journal of Applied Islamic Economics and Finance, 2022)
This study examines the factors that influence the distribution of financing in islamic rural banks in Indonesia. These factors include Third Party Funds (DPK), Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Return on Assets (ROA), and Rasio efisiensi Operasional (REO). The population and sample used in this study are all of Islamic rural banks in Indonesia. The data used is secondary data in annual financial reports published by financial servives authority of Indonesia on it is official website for 2015-2020 period. Quantitative is the method used in this research with multiple regression processed through the Eviews version 9 program as the data processing application. The results of the analysis show that partially DPK, ROA, and REO have positive and significant influence to financing, while CAR and NPF partially have no influence to financing.